Nexus Resources Efficiency Assessment and Management towards Transition to Sustainable Bioeconomy in Thailand - Pitak Ngammuangtueng (2020)
© 2020 Elsevier B.V. This research developed an analysis tool on nexus resource efficiency and management towards bioeconomy. Its application has been demonstrated in the Thai cassava and sugarcane supply chains combining Material Flow Analysis, nexus assessment, and Eco-efficiency. The results revealed that doubling the feedstock and maximizing biochemical/biomaterial production has the highest value addition and also the highest eco-efficiency among all the options considered. However, it required at least 2-3 times the amount of water and energy for irrigation and processing as compared to the base case. A more detailed analysis of regional resource availability and security needs to be further conducted to support the decision-making process. The scenario that has no increase in feedstock production but allocates the cassava used for export as feed to use for feedstock for biochemical/biomaterial instead can also have excellent economic returns and eco-efficiency with much lower resource consumption. Feedstock cultivation yield and lactic acid production efficiency are critical factors in reducing overall supply chain resource consumption. Decision-makers need to prepare a strategic plan for optimum resource allocation towards maintaining a less resource-intensive society.